COLLABORATIVE GOVERNANCE DALAM UPAYA PERLINDUNGAN PEREMPUAN DAN ANAK TERHADAP KEKERASAN SEKSUAL DIKOTA DENPASAR - Nursina, Nursina; Latupeirissa, Jonathan Jacob Paul; Joniarta, I Wayan; Antari, Ni Putu Bayu Widhi (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
Sexual violence against women and children is a serious issue that continues to increase in various regions, including Denpasar. Addressing this violence requires the involvement of various stakeholders in a collaborative governance approach. This study aims to analyze the application of collaborative governance in protecting women and children from sexual violence in Denpasar. The research method used a qualitative approach through observation, interviews, and documentation. The results of this study indicate that collaboration between the DP3AP2KB (Regional Empowerment and Child Protection Agency), the UPTD PPA (Regional Empowerment and Child Protection Unit), the Bali Seruti Foundation, and the community has been effective through face-to-face dialogue, trust-building, commitment to the process, shared understanding, and intermediate outcomes, as indicated by Ansell & Gash (2008). However, challenges remain, such as limited resources, increased human resource capacity, and the need to optimize community involvement in reporting and prevention. The study confirms that cross-sector collaboration plays a crucial role in increasing the effectiveness of protecting women and children from sexual violence in Denpasar.